The Giza pyramid: learning from this megaproject. Issue 3 (21st June 2019) - Procter, Chris; Kozak-Holland, Mark
Abstract : Purpose: The purpose of this paper is to demonstrate the contemporary relevance of the management of the Great Pyramid of Giza project. Design/methodology/approach: The paper uses evidence from the literature from many disciplines concerning both the objectives and construction of the pyramid. It relates this to recent discussion concerned with the issues faced in megaproject management, which are core to the discussion of success and failure. Findings: The analysis shows the significance of the "break-fix model" of megaproject management and how having a sequence of megaprojects builds management through a learning process. It demonstrates the significance of innovation arising from the experience of previous projects in solving major technical challenges and illustrates the importance of the organisation and ethical management of a substantial workforce. Research limitations/implications: There is very limited reliable documentary evidence from the time of the construction of Giza (c.2560 BCE). Many sources concerning ancient Egypt are still widely contested. However, the use of research from a combination of disciplines demonstrates the relevance of the project and the importance of learning from history to contemporary project management. Originality/value: The authors believe that this is the first paper to analyse the Giza pyramid project from a project management perspective. This was arguably the most significant construction project of ancient history and the paper explains the lessons, which can be learned, which are very significant to today's megaprojects.